Efficacy of Pre- and Post-Transplant Herbicides in Tobacco (Nicotiana tabacum L.) Influenced by Precipitation and Soil Type - Zvonko Pacanoski; Danijela Šikuljak; Ana Anđelković; Snežana Janković; Slađan Stanković; Divna Simić; Dušan Nikolić (Agronomy)
Field trials were carried out over two tobacco cropping seasons (2020 and 2021) to assess the effectiveness of soil (PRE-T) and post-transplant (POST-T (OT)) herbicides in a tobacco crop, depending on rainfall and the type of soil. The effectiveness of PRE-T and POST-T (OT) herbicides alternated according to the presence of weeds, treatments, the region, and years. Unpredictable meteorological conditions throughout the two study years likely influenced the control of weeds. An unusually moist May in 2020 with a precipitation of 29 mm in the first WA PRE-T before the emergence of weeds generated the leaching of the PRE-T herbicide from the surface of the soil, which was likely the most probable reason for the reduced effectiveness of PRE-T-applied herbicides (less than 77%) in comparison to the POST-T (OT) application treatment in 2020 in the Prilep region. Conversely, the restricted rainfall after PRE-T and POST-T (OT) application may have caused the unsatisfactory efficacy of both PRE-T and POST-T (OT) herbicide treatments in the Titov Veles region in 2021 (less than 78 and 80%, respectively) in comparison with 2020. Excessive rain immediately after PRE-T and POST-T (OT) application resulted in the injury of tobacco plants in the Prilep region in 2020 and 2021, which was between 8 and 25%, and 7 and 22%, respectively, after seven DAHAs across both treatments. The injuries caused by pendimethalin and metolachlor were more serious. The yields of tobacco after both PRE-T and POST-T treatment in each region typically reflect the overall effectiveness of weed control and the extent of tobacco crop injury.